Description of a new species of the subgenus Hippomias Yunakov, 2006 in the genus Brachysomus Schoenherr, 1823 (Coleoptera: Curculionidae: Entiminae) from Lebanon - Szénási, Valentin; Németh, Tamás (Zootaxa, 2019)
Brachysomus (Hippomias) tannourinensis sp. nov. is described from Lebanon, compared with similar Brachysomus species, and its main diagnostic features are figured. The new species was discovered at the ancient cedar forest of Tannourine as the first known representative of the genus Brachysomus in Lebanon. It is easily recognizable by the body vestiture consisting of two types of scales, the prolonged shape of the rostrum, and the parallel-sided penis.